Maternal milk supplementation among pregnant women in Kuantan, Pahang - Baba, Nor Faezah; Abu Samah, Nur Faten; Mohd Shukri, Nor Azwani (IIUM Press, International Islamic University Malaysia, 2018)
Pregnancy is a crucial period for mothers to ensure proper weight gain and adequate nutrients intake. This is important for healthy fetal growth. There are increasing numbers of maternal milk supplementation which claimed to provide the essential nutrients that are needed during pregnancy such as iron, folic acid, and docohexanoic acid. The current study was conducted to assess the practice of maternal milk supplementation (MMS) intake among pregnant women in Kuantan, Pahang, and whether its consumption plays a role in meeting the requirement for total energy and nutrients intake. Questionnaires regarding intake of MMS were distributed to 150 subjects to observe the prevalence of its consumption. From that, 54 subjects (from 2nd and 3rd trimesters) were interviewed to obtain their diet history using multiple pass 24-hours dietary recall method to examine their energy and nutrients intake in comparison to the Recommended Nutrients Intake for Malaysia (RNI), 2005. It was found that almost three quarter (70%) of the subjects consumed MMS. Women who consumed MMS during pregnancy were found to be significantly younger, of lower parity as well as lower pre-pregnancy body mass index. It was also shown that the women’s dietary intakes without MMS supplementation were insufficient to meet the RNI for total energy and some selected nutrients, except for iron and folic acid intakes. The results of this study indicate that MMS could play a role in increasing the dietary intakes of total energy, protein and calcium of pregnant women who are not consuming these nutrients sufficiently as recommended